A secure and efficient remote patient‐monitoring authentication protocol for cloud‐IoT. (15th April 2020) - Alzahrani, Bander A.; Irshad, Azeem; Alsubhi, Khalid; Albeshri, Aiiad
Summary: The ongoing Cloud‐IoT (Internet of Things)–based technological advancements have revolutionized the ways in which remote patients could be monitored and provided with health care facilities. The real‐time monitoring of patient's health leads to dispensing the right medical treatment at the right time. The health professionals need to access patients' sensitive data for such monitoring, and if treated with negligence, it could also be used for malevolent objectives by the adversary. Hence, the Cloud‐IoT–based technology gains could only be conferred to the patients and health professionals, if the latter authenticate one another properly. Many authentication protocols are proposed for remote patient health care monitoring, but with limitations. Lately, Sharma and Kalra (DOI: 10.1007/s40998‐018‐0146‐5) present a remote patient‐monitoring authentication scheme based on body sensors. However, we discover that the scheme still bears many drawbacks including stolen smart card attack, session key compromise, and user impersonation attacks. In view of those limitations, we have designed an efficient authentication protocol for remote patient health monitoring that counters all the above‐mentioned drawbacks. Moreover, we prove the security features of our protocol using BAN logic‐based formal security analysis and validate the results in ProVerif automated security tool. Abstract : The health professionals need to access patients' sensitive data for such monitoring, and if treated with negligence, it may be abused for malicious objectives by the adversary. Thus, Cloud‐IoT–based technology gains for patient's health monitoring could only be delivered to stakeholders, if the participating entities authenticate one another properly. In this context, we reviewed and identified several attacks in Sharma and Kalra health‐monitoring authentication scheme and proposed a secure and efficient authentication protocol, supported with formal security analysis‐based proofs.